THE METHOD OF WAVE LETS CONSTRUCTION BY TRANSFORMATION OF A GRAPH OF POWER FUNCTION FOR EDGE DETECTION - Polyakova, Marina; Krylov, Victor; Volkova, Natalya (International Journal of Computing, 2014)
In this paper the method to construct the improved wavelets by transformation of a graph of power function is developed for the edge detection.